2023
DOI: 10.1186/s13256-022-03710-2
|View full text |Cite
|
Sign up to set email alerts
|

The reporting requirements of case reports and adherence of case report reporting guidelines in medical journals: an analysis of the authors’ guide sections

Abstract: Background Owing to the growth of case reports and changes in the policy of journals in publishing this evidence, the need to standardize them is felt more than before. Therefore, in this study, the authors’ guide of medical journals indexed in the Scopus database that published most of the case reports has been analyzed to identify the reporting requirements and emerging case report types. Methods A total of 50 journals were selected from the Scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…The CARE guidelines include a checklist with items such as deidentified patient information, informed consent, and patient perspective on the treatment they received [ 10 ]. While multiple guidelines exist, adherence is not mandatory; 1 study found that out of 50 journals, 76% did not adhere to any guidelines for publication of personal information [ 11 ]. Another study investigating CARE guideline adherence in 36 Indian medical journals found that only a third exhibited average adherence and that overall there was poor reporting of subject-informed consent [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CARE guidelines include a checklist with items such as deidentified patient information, informed consent, and patient perspective on the treatment they received [ 10 ]. While multiple guidelines exist, adherence is not mandatory; 1 study found that out of 50 journals, 76% did not adhere to any guidelines for publication of personal information [ 11 ]. Another study investigating CARE guideline adherence in 36 Indian medical journals found that only a third exhibited average adherence and that overall there was poor reporting of subject-informed consent [ 7 ].…”
Section: Introductionmentioning
confidence: 99%